2017
DOI: 10.1002/jnr.24035
|View full text |Cite
|
Sign up to set email alerts
|

α4βδ‐GABAA receptors in dorsal hippocampal CA1 of adolescent female rats traffic to the plasma membrane of dendritic spines following voluntary exercise and contribute to protection of animals from activity‐based anorexia through localization at excitatory synapses

Abstract: In hippocampal CA1 of adolescent female rodents, α4βδ-GABA receptors (α4βδ-GABA Rs) suppress excitability of pyramidal neurons through shunting inhibition at excitatory synapses. This contributes to anxiolysis of stressed animals. Socially isolated adolescent female rats with 8 days of wheel access, the last 4 days of which entail restricted food access, have been shown to exhibit excessive exercise, choosing to run instead of eat (activity-based anorexia [ABA]). Upregulation of α4βδ-GABA Rs in the dorsal hipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 59 publications
3
13
0
Order By: Relevance
“…Up-regulation of α4-subunits of GABA A Rs was previously shown to occur within the hippocampus of adolescent female ABA rats (Aoki et al, 2012; Aoki et al, 2014; Aoki et al, 2017) and mice (Wable et al, 2015a). However, none of those studies compared a4-immunoreactivity between the sexes.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Up-regulation of α4-subunits of GABA A Rs was previously shown to occur within the hippocampus of adolescent female ABA rats (Aoki et al, 2012; Aoki et al, 2014; Aoki et al, 2017) and mice (Wable et al, 2015a). However, none of those studies compared a4-immunoreactivity between the sexes.…”
Section: Resultsmentioning
confidence: 93%
“…At puberty onset, its expression in dorsal CA1 of female rodents increases transiently in response to the rapid rise, then the decline in the level of allopregnanolone (Shen et al, 2007; Aoki et al, 2012). ABA increases alpha4betadelta-GABA A R expression at excitatory synapses of stratum radiatum of dorsal hippocampal CA1 of adolescent female rodents (Aoki et al, 2012; Wable et al, 2015a; Aoki et al, 2017). However, whether ABA increases alpha4betadelta-GABA A R expression in adolescent males remained unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescence is a period of psychiatric vulnerability which, in turn, is influenced by anxiety that is proposed to be regulated more by the ventral than the dorsal hippocampus (Bannerman et al, ; McHugh, Deacon, Rawlins, & Bannerman, ). However, we have data indicating otherwise (Aoki, Chen, Chowdhury, & Piper, ). It has also been shown that dorsal and ventral hippocampal lesions interact with puberty to result in different behavioral deficits in adulthood (Lipska, Jaskiw, & Weinberger, ; Pacteau, Einon, & Sinden, ).…”
Section: Introductionmentioning
confidence: 89%
“…Vulnerability to AN might vary due to individual differences in any of these responses to caloric restriction, differences that could result from variation in dopamine genes or genes that modulate dopamine (e.g., leptin, insulin, ghrelin, glucocorticoid, orexin). Of course, factors independent of dopamine may also modulate vulnerability [e.g., (100)].…”
Section: Dopamine and An Vulnerabilitymentioning
confidence: 99%